2019
DOI: 10.1016/j.ajodo.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Anterior open bite due to idiopathic condylar resorption during orthodontic retention of a Class II Division 1 malocclusion

Abstract: A common dilemma when treating anterior open bite is understanding its etiology. Idiopathic condylar resorption (ICR) can cause open bite in affected individuals. Although it is prudent to not treat patients with ICR until active resorption has ceased, orthodontists may begin treating them because anterior open bite from ICR may not appear before or during their orthodontic treatment. This article reports a 12-year-old female who was diagnosed with ICR 10 months after completion of her orthodontic treatment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The previous study just included one patient and used a two-dimensional radiograph for the evaluation [16]. Park JH, et al, [50] reported a case (12-year-old female) diagnosed with ICR 10 months after orthodontic treatment completion of skeletal class II division 1 malocclusion. They concluded that orthodontists have to closely monitor the patients and offer detailed treatment options to patients with risk factors for ICR that might develop at any stage of orthodontic treatment.…”
Section: D Condylar Resorption During Orthodontic and Orthognathic Surgerymentioning
confidence: 99%
“…The previous study just included one patient and used a two-dimensional radiograph for the evaluation [16]. Park JH, et al, [50] reported a case (12-year-old female) diagnosed with ICR 10 months after orthodontic treatment completion of skeletal class II division 1 malocclusion. They concluded that orthodontists have to closely monitor the patients and offer detailed treatment options to patients with risk factors for ICR that might develop at any stage of orthodontic treatment.…”
Section: D Condylar Resorption During Orthodontic and Orthognathic Surgerymentioning
confidence: 99%
“…In general, the treatment objectives for ICR are to relieve joint pain, establish ideal joint function, correct the anterior openbite malocclusion, and improve facial esthetics [8]. Consistent among several articles reviewed was the emphasis placed on the importance of waiting to begin invasive treatment until after the active resorption had ceased, unless the purpose of treatment is to halt the progression of ICR [4,9]. Treatments performed to stop active resorption caused by ICR include the initiation of splint use, removal of the hyperplastic synovium, and condylectomy with a costochondral graft [4].…”
Section: Treatment Goals and Optionsmentioning
confidence: 99%
“…Additionally, nonsteroidal anti-inflammatory drugs, therapeutic exercises, intraarticular space steroid injections, and Vitamin D and calcium supplementation to increase bone density during the active resorption stage may be recommended [2,10]. Other noninvasive treatment options can include exercise, manual therapy, and relaxation training [9]. While nonsurgical, conservative options aim to achieve pain relief and remission of pathological changes first, orthodontic therapy can provide improvements in occlusion but is limited in its ability to drastically improve facial esthetics [8].…”
Section: Treatment Goals and Optionsmentioning
confidence: 99%
“…In addition, injuries of the gingival margin by the clasp's retentive arm when swallowing and chewing, as well as injuries of the interdental papilla and gingival margin-which are caused by the base of the removable denture-are often developed. [8][9][10][11][12] In cases of suboptimal positioning of the denture support elements when using rigid lock clasps, end defects of the dental alignment may develop, while the negative impact of removable dentures is increased in the absence of occlusal contacts in the area of remaining natural teeth. [13][14][15] The most frequent cause of damage to the oral mucosa is chronic mechanical injury, including by partial removable denture.…”
Section: Introductionmentioning
confidence: 99%
“…16,[18][19][20] Bacterial infection is considered to be the most important factor contributing to denture failure, and the microbiota includes Prevotella intermedia, Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Bacterioides for sythus, Treponema denticola, Prevotella nigrescens, Pepto streptococcus micros, Fusobacterium nucleatum, and several other microorganisms causing peri-implantitis. 12,14,21,22 Bacteria are a key etiological factor in periodontal disease, so the composition of the microbiota in the areas surrounding the denture may have a significant impact on the condition of this area in the following. 23 Submucosal microflora in areas with clinically healthy margins surrounding the denture is usually represented by gram-positive cocci and rod bacteria.…”
Section: Introductionmentioning
confidence: 99%